2007
DOI: 10.1177/152660280701400417
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Coronary Flow Reserve following Stent Implantation in the Swine Descending Thoracic Aorta

Abstract: Stent deployment in the normal swine DTA produces a significant immediate decrease in CFR, which is attenuated 3 weeks later. The clinical impact of CFR changes following DTA endografting remain to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Aortic stiffening is known to play a significant role in cardiovascular disease development and progression [8,9]. Several preclinical studies have reported on acute stiffening of the aorta following TEVAR, resulting in acute elevated pulse pressure, hypertension, reduced coronary perfusion and eventually heart failure [10,11]. These findings have been confirmed by computational studies using simplified blood flow models [12].…”
Section: Introductionmentioning
confidence: 89%
“…Aortic stiffening is known to play a significant role in cardiovascular disease development and progression [8,9]. Several preclinical studies have reported on acute stiffening of the aorta following TEVAR, resulting in acute elevated pulse pressure, hypertension, reduced coronary perfusion and eventually heart failure [10,11]. These findings have been confirmed by computational studies using simplified blood flow models [12].…”
Section: Introductionmentioning
confidence: 89%
“…The aortic compliance serves a critical function to reduce the impedance and workload of cardiac ejection ( 46 ). Preclinical ( 30 , 47 49 ) and preliminary clinical ( 50 ) studies have reported on acute stiffening of the aorta following TEVAR, resulting in acute elevated pulse pressure, hypertension, reduced coronary perfusion, and eventually heart failure ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies, in addition to clinical trials, show that stent-grafts increase the pulse wave velocity (PWV) of the aorta (de Beaufort et al 2017;Kadoglou et al 2012Kadoglou et al , 2014Liam Morris et al 2013;Van Noort et al 2018), which is an independent risk factor for cardiac failure (Ben-Shlomo et al 2014). Importantly, the Windkessel effect is diminished following stenting (Nauta et al 2017;Belz 1995), and increased PWV has been directly linked to cardiac death via a complex cascade of increased pulse pressure (Benetos et al 1997), increased left-ventricular afterload and decreased coronary flow (Spadaccio et al 2016;Zacharoulis et al 2007), and ultimately left ventricular hypertrophy (Kim et al 1995;Morita et al 2002).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%